Preparation method and application of SnIn4S8-coated FeNi2P hollow nanorod composite material

By growing SnIn4S8 on FeNi2P surface, a heterostructured SnIn4S8@FeNi2P hollow nanorod composite material was constructed, which solved the problems of low light utilization rate of the photocatalyst and poor structural stability, and achieved efficient photocatalytic hydrogen production performance and good cycle stability sex.

CN119114118AActive Publication Date: 2024-12-13QINGDAO UNIV OF SCI & TECH

Patent Information

Application Number
CN202411260215.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

In the photocatalytic hydrogen production process, existing photocatalysts have problems such as low catalyst light utilization, poor structural stability and low carrier separation efficiency. It is necessary to explore photocatalysts with high activity and high stability.

Method used

FeNi2-MIL-88 nanorods were synthesized by hydrothermal method, and then FeNi2P was obtained by gas-phase phosphating method. Then, SnIn4S8 nanosheets were grown in situ on the FeNi2P surface to form SnIn4S8@FeNi2P hollow nanorod composite material, and a heterostructure was constructed to inhibit photogenesis. Recombination of electrons and holes.

Benefits of technology

The photocatalytic hydrogen production performance is significantly improved, the preparation process is simple and time-consuming, and the obtained SnIn4S8@FeNi2P composite material has good cycle stability and efficient hydrolysis hydrogen production performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005035332840000011
    Figure HDA0005035332840000011
  • Figure HDA0005035332840000012
    Figure HDA0005035332840000012
  • Figure HDA0005035332840000013
    Figure HDA0005035332840000013
Patent Text Reader

Abstract

The invention provides a SnIn4S8-coated FeNi2P hollow nanorod composite material and a preparation method thereof. The photocatalytic hydrogen production performance and the stability of the SnIn4S8-coated FeNi2P hollow nanorod composite material are researched. The preparation method of the SnIn4S8-coated FeNi2P comprises the following steps: synthesizing a FeNi2-MIL-88 nanorod with a hollow structure by adopting a hydrothermal method, and then obtaining the FeNi2P by adopting a gas phase phosphating method. And finally, coating the surface of the FeNi2P with SnIn4S8 by virtue of an in-situ growth method, so as to obtain the SnIn4S8-coated FeNi2P hollow nanorod composite material. The result shows that the hydrogen production amount of the SnIn4S8-coated FeNi2P within 3 hours reaches 18083.93 [mu] mol / g, and the SnIn4S8-coated FeNi2P has good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and in particular to a SnIn 4 S 8 @FeNi 2 Preparation and photocatalytic application of P hollow nanorod composites. Background Art

[0002] The shortage of fossil fuels and environmental pollution have prompted the continuous research and development of new renewable energy sources. Among them, hydrogen energy has attracted much attention due to its advantages such as clean, zero pollution and non-toxicity. Since solar energy resources are abundant and can be obtained locally, the use of solar energy to produce hydrogen has a good prospect. Under light conditions, photocatalysts can use solar energy to split water to produce hydrogen, but in this process there are still problems such as low catalyst light utilization, poor structural stability, and low carrier separation efficiency. Therefore, exploring photocatalysts with high activity and high stability has become a research hotspot in this field.

[0003] Hollow structured metal organic frameworks (MOFs) are a type of porous material with low density and stable morphology. The hollow structure improves the light-harvesting ability and reduces the migration distance of the carrier. Transition metal phosphides derived from MOFs can retain their hollow porous structure and improve their stability, and have been widely used in the field of photocatalytic hydrogen production. However, transition metal phosphides still have disadvantages such as poor dispersibility and low carrier separation rate. Their catalytic performance can be improved by ion doping, morphology regulation, heterostructure construction, and co-catalyst loading. Among them, constructing a heterostructure is an effective way to improve the efficiency of photogenerated carrier separation.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] In order to solve the shortcomings of the prior art, the present invention firstly adopts a hydrothermal method to synthesize a hollow structure FeNi 2 -MIL-88 nanorods, and then FeNi was obtained by vapor phase phosphating 2 P, and secondly, SnIn with high electronegativity and strong light absorption ability 4 S 8 Nanosheets grown in situ on FeNi 2 P surface, forming SnIn 4 S 8 @FeNi 2 P hollow nanorod composites. The constructed heterostructure effectively inhibits the recombination of photogenerated electrons and holes, thereby improving the photocatalytic hydrogen production performance.

[0006] Specifically, the present invention provides a SnIn 4 S8 @FeNi 2 P hollow nanorod composites, first synthesized FeNi 2 -MIL-88 nanorods, which were then phosphated to form FeNi 2 P, finally in FeNi 2 In situ growth of a SnIn layer on the P surface 4 S 8 , get SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

[0007] Another object of the present invention is to provide a SnIn 4 S 8 @FeNi 2 The preparation method of the P hollow nanorod composite material specifically comprises the following steps:

[0008] (1) 1,4-Benzenedicarboxylic acid, ferric chloride and nickel nitrate hexahydrate are dissolved in dimethylacetamide in sequence and stirred to fully dissolve. The above solution is added into a high pressure reactor and heated at 150° C. for 3 h. The product is centrifuged, washed and dried to obtain FeNi 2 -MIL-88 hollow nanorods;

[0009] (2) FeNi 2 -MIL-88 nanorods and anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h to obtain FeNi 2 P hollow nanorods;

[0010] (3) FeNi 2 The P hollow nanorods were dissolved in ethanol and ultrasonicated for 10 min. Tin tetrachloride pentahydrate and indium trichloride tetrahydrate were added in sequence and stirred to dissolve. Then, thioacetamide was added. The mixed solution was heated under reflux for 3 h. The product was centrifuged, washed and dried to obtain SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

[0011] Preferably, in step (1), the molar ratio of 1,4-phthalic acid, ferric chloride and nickel nitrate hexahydrate is (2-8):1:(1-2).

[0012] Preferably, in step (2), FeNi 2The mass ratio of P to anhydrous sodium hypophosphite is 1:(1-3).

[0013] Preferably, the heating rate of high temperature calcination in step (2) is 1 to 5°C / min.

[0014] Preferably, in step (3), the molar ratio of tin tetrachloride pentahydrate, indium trichloride tetrahydrate and thioacetamide is 0.25:1:(2-5).

[0015] Preferably, in step (3), FeNi 2 The P content is 2-12 g / L.

[0016] Another object of the present invention is to provide a SnIn 4 S 8 @FeNi 2 Application of P hollow nanorod composites in photocatalytic water splitting to produce hydrogen.

[0017] A 300W full-spectrum Xe lamp was used as the light source to produce hydrogen by photocatalysis at a certain wavelength (≥420nm). 10mg of photocatalyst was added to a glass container containing 90mL of deionized water, 10mL of triethanolamine, and 0.033g of eosin. During the test, the system temperature was maintained at around 6°C. Finally, the data was analyzed using a gas chromatograph (GC-2014).

[0018] Compared with the prior art, the SnIn 4 S 8 @FeNi 2 P hollow nanorod composite material, the preparation time is short and the method is simple, the SnIn prepared by the present invention 4 S 8 @FeNi 2 As a photocatalyst, the P hollow nanorod composite material has significantly improved hydrogen production performance by water splitting and has good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The FeNi described in Example 1 2 - Transmission electron microscope photo of MIL-88.

[0020] Figure 2 SnIn described in Example 3 4 S 8 @FeNi 2 Scanning electron micrograph of P.

[0021] Figure 3 Figure 2 is a diagram of photocatalytic hydrogen production of the catalyst materials prepared in Examples 2 and 3.

[0022] Figure 4 SnIn described in Example 3 4 S 8 @FeNi 2 XRD spectrum of P. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific embodiments:

[0024] Example 1

[0025] This embodiment provides a FeNi 2 -The preparation method of MIL-88 nanorods comprises the following steps:

[0026] 1 mmol of 1,4-benzenedicarboxylic acid, 0.33 mmol of ferric chloride and 0.66 mmol of nickel nitrate hexahydrate were dissolved in 30 mL of dimethylacetamide in sequence and stirred to fully dissolve. The above solution was added to a high-pressure reactor and heated at 150°C for 3 h. The product was centrifuged, washed and dried to obtain FeNi 2 -MIL-88 hollow nanorods.

[0027] Example 2

[0028] This embodiment provides a FeNi 2 The preparation method of P comprises the following steps:

[0029] 30 mg of FeNi 2 -MIL-88 nanorods and 90 mg of anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h at a heating rate of 3 °C / min to obtain FeNi 2 P hollow nanorods.

[0030] Example 3

[0031] This embodiment provides a SnIn 4 S 8 @FeNi 2 The preparation method of the P hollow nanorod composite material comprises the following steps:

[0032] (1) 1 mmol of 1,4-benzenedicarboxylic acid, 0.33 mmol of ferric chloride, and 0.66 mmol of nickel nitrate hexahydrate were dissolved in 30 mL of dimethylacetamide in sequence, stirred to fully dissolve, and the above solution was added to a high-pressure reactor, heated at 150° C. for 3 h, and the product was centrifuged, washed, and dried to obtain FeNi 2 -MIL-88 hollow nanorods.

[0033] (2) 30 mg of FeNi 2 -MIL-88 nanorods and 90 mg of anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h at a heating rate of 3 °C / min to obtain FeNi 2 P hollow nanorods.

[0034] (3) 100 mg of FeNi 2 The P hollow nanorods were dissolved in 12.5 mL of ethanol and ultrasonicated for 10 min. 0.125 mmol of tin tetrachloride pentahydrate and 0.5 mmol of indium trichloride tetrahydrate were added in sequence and stirred to dissolve. Then 1.5 mmol of thioacetamide was added. The mixed solution was heated under reflux for 3 h. The product was centrifuged, washed and dried to obtain SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

[0035] The FeNi prepared in Example 1 2 -MIL-88 nanorods were tested by transmission electron microscopy. The test results are shown in Figure 1 As shown in the figure, FeNi 2 -MIL-88 exhibits a hollow nanorod structure.

[0036] The SnIn prepared in Example 3 4 S 8 @FeNi 2 P was tested by scanning electron microscope, and the test results are shown in Figure 2 , as shown in the figure, SnIn 4 S 8 Successfully coated on FeNi 2 P surface and SnIn 4 S 8 @FeNi 2 P still maintains the hollow nanorod structure.

[0037] The photocatalytic hydrogen production performance of the products obtained in Examples 2 and 3 was tested. The specific method is: using a 300W full-spectrum Xe lamp as the light source, photocatalytic hydrogen production was performed at a certain wavelength (≥420nm). 10mg of photocatalyst was added to a glass container containing 90mL of deionized water, 10mL of triethanolamine, and 0.033g of eosin. During the test, the system temperature was maintained at around 6°C. Finally, the data was analyzed using a gas chromatograph (GC-2014). The results are shown in Figure 3 , as shown in the figure:

[0038] 1. When the FeNi prepared in Example 2 2 When P was used as the photocatalyst, the photocatalytic hydrogen production was 6964.99 μmol / g within 3 hours;

[0039] 2. When the SnIn prepared in Example 3 is used 4 S 8 @FeNi 2 When P was used as the photocatalyst, the photocatalytic hydrogen production was 18083.93 μmol / g within 3 hours.

[0040] The SnIn prepared in Example 3 4 S 8 @FeNi 2 P composite material was subjected to XRD test, and the test results are shown in Figure 4 , as shown in the figure, in SnIn 4 S 8 @FeNi 2 In the XRD pattern of P, it is observed that 4 S 8 and FeNi 2 The diffraction peaks corresponding to P and no other impurity peaks further confirm that SnIn 4 S 8 @FeNi 2 P composite material was successfully prepared.

[0041] The above experimental results show that FeNi 2 P surface modified SnIn 4 S 8 After that, the photocatalytic hydrogen production performance was significantly improved, proving that FeNi 2 P and SnIn 4 S 8 The composite can effectively enhance the photocatalytic hydrogen production performance.

[0042] Example 4

[0043] This embodiment provides a SnIn 4 S 8 @FeNi 2The preparation method of the P hollow nanorod composite material comprises the following steps:

[0044] (1) 1 mmol of 1,4-benzenedicarboxylic acid, 0.33 mmol of ferric chloride, and 0.66 mmol of nickel nitrate hexahydrate were dissolved in 30 mL of dimethylacetamide in sequence, stirred to fully dissolve, and the above solution was added to a high-pressure reactor, heated at 150° C. for 3 h, and the product was centrifuged, washed, and dried to obtain FeNi 2 -MIL-88 hollow nanorods.

[0045] (2) 30 mg of FeNi 2 -MIL-88 nanorods and 60 mg of anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h at a heating rate of 3 °C / min to obtain FeNi 2 P hollow nanorods.

[0046] (3) 100 mg of FeNi 2 The P hollow nanorods were dissolved in 12.5 mL of ethanol and ultrasonicated for 10 min. 0.125 mmol of tin tetrachloride pentahydrate and 0.5 mmol of indium trichloride tetrahydrate were added in sequence and stirred to dissolve. Then 1.5 mmol of thioacetamide was added. The mixed solution was heated under reflux for 3 h. The product was centrifuged, washed and dried to obtain SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

[0047] Example 5

[0048] This embodiment provides a SnIn 4 S 8 @FeNi 2 The preparation method of the P hollow nanorod composite material comprises the following steps:

[0049] (1) 2 mmol of 1,4-benzenedicarboxylic acid, 0.33 mmol of ferric chloride, and 0.66 mmol of nickel nitrate hexahydrate were dissolved in 30 mL of dimethylacetamide in sequence, stirred to fully dissolve, and the above solution was added to a high-pressure reactor, heated at 150° C. for 3 h, and the product was centrifuged, washed, and dried to obtain FeNi 2 -MIL-88 hollow nanorods.

[0050] (2) 30 mg of FeNi 2-MIL-88 nanorods and 90 mg of anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h at a heating rate of 1 °C / min to obtain FeNi 2 P hollow nanorods.

[0051] (3) 100 mg of FeNi 2 The P hollow nanorods were dissolved in 12.5 mL of ethanol and ultrasonicated for 10 min. 0.125 mmol of tin tetrachloride pentahydrate and 0.5 mmol of indium trichloride tetrahydrate were added in sequence and stirred to dissolve. Then 1.5 mmol of thioacetamide was added. The mixed solution was heated under reflux for 3 h. The product was centrifuged, washed and dried to obtain SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

[0052] Example 6

[0053] This embodiment provides a SnIn 4 S 8 @FeNi 2 The preparation method of the P hollow nanorod composite material comprises the following steps:

[0054] (1) 1 mmol of 1,4-benzenedicarboxylic acid, 0.33 mmol of ferric chloride, and 0.66 mmol of nickel nitrate hexahydrate were dissolved in 30 mL of dimethylacetamide in sequence, stirred to fully dissolve, and the above solution was added to a high-pressure reactor, heated at 150° C. for 3 h, and the product was centrifuged, washed, and dried to obtain FeNi 2 -MIL-88 hollow nanorods.

[0055] (2) 30 mg of FeNi 2 -MIL-88 nanorods and 90 mg of anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h at a heating rate of 3 °C / min to obtain FeNi 2 P hollow nanorods.

[0056] (3) 100 mg of FeNi 2The P hollow nanorods were dissolved in 12.5 mL of ethanol and ultrasonicated for 10 min. 0.125 mmol of tin tetrachloride pentahydrate and 0.5 mmol of indium trichloride tetrahydrate were added in sequence and stirred to dissolve. Then 1.0 mmol of thioacetamide was added. The mixed solution was heated under reflux for 3 h. The product was centrifuged, washed and dried to obtain SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

[0057] Example 7

[0058] This embodiment provides a SnIn 4 S 8 @FeNi 2 The preparation method of the P hollow nanorod composite material comprises the following steps:

[0059] (1) 1 mmol of 1,4-benzenedicarboxylic acid, 0.33 mmol of ferric chloride, and 0.66 mmol of nickel nitrate hexahydrate were dissolved in 30 mL of dimethylacetamide in sequence, stirred to fully dissolve, and the above solution was added to a high-pressure reactor, heated at 150° C. for 3 h, and the product was centrifuged, washed, and dried to obtain FeNi 2 -MIL-88 hollow nanorods.

[0060] (2) 30 mg of FeNi 2 -MIL-88 nanorods and 90 mg of anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h at a heating rate of 3 °C / min to obtain FeNi 2 P hollow nanorods.

[0061] (3) 150 mg of FeNi 2 The P hollow nanorods were dissolved in 12.5 mL of ethanol and ultrasonicated for 10 min. 0.125 mmol of tin tetrachloride pentahydrate and 0.5 mmol of indium trichloride tetrahydrate were added in sequence and stirred to dissolve. Then 1.5 mmol of thioacetamide was added. The mixed solution was heated under reflux for 3 h. The product was centrifuged, washed and dried to obtain SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

[0062] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A SnIn 4 S 8 @FeNi 2 Preparation method of P hollow nanorod composite material, It is characterized in that The following steps are involved: (1) 1,4-Benzenedicarboxylic acid, ferric chloride and nickel nitrate hexahydrate are dissolved in dimethylacetamide in sequence and stirred to fully dissolve. The above solution is added into a high pressure reactor and heated at 150° C. for 3 h. The product is centrifuged, washed and dried to obtain FeNi 2 -MIL-88 hollow nanorods; (2) FeNi 2 -MIL-88 nanorods and anhydrous sodium hypophosphite were placed in two porcelain boats respectively. The porcelain boat containing anhydrous sodium hypophosphite was placed at the air inlet end of the tube furnace. 2 -MIL-88 porcelain boat is placed at the outlet of the tube furnace. 2 The temperature was raised to 350 °C and maintained for 2 h to obtain FeNi 2 P hollow nanorods; (3) FeNi 2 The P hollow nanorods were dissolved in ethanol and ultrasonicated for 10 min. Tin tetrachloride pentahydrate and indium trichloride tetrahydrate were added in sequence and stirred to dissolve. Then, thioacetamide was added. The mixed solution was heated under reflux for 3 h. The product was centrifuged, washed and dried to obtain SnIn 4 S 8 @FeNi 2 P hollow nanorod composites.

2. SnIn as claimed in claim 1 4 S 8 @FeNi 2 Preparation method of P, It is characterized in that In the step (1), the molar ratio of 1,4-phthalic acid, ferric chloride and nickel nitrate hexahydrate is (2-8):1:(1-2).

3. SnIn as claimed in claim 1 4 S 8 @FeNi 2 Preparation method of P, It is characterized in that In the step (2), FeNi 2 -The mass ratio of MIL-88 to anhydrous sodium hypophosphite is 1:(1-3).

4. SnIn as claimed in claim 1 4 S 8 @FeNi 2 Preparation method of P, It is characterized in that The heating rate of high temperature calcination in step (2) is 1 to 5°C / min.

5. SnIn as claimed in claim 1 4 S 8 @FeNi 2 Preparation method of P, It is characterized in that In the step (3), the molar ratio of tin tetrachloride pentahydrate, indium trichloride tetrahydrate and thioacetamide is 0.25:1:(2-5).

6. SnIn as claimed in claim 1 4 S 8 @FeNi 2 Preparation method of P, It is characterized in that In the step (3), FeNi 2 The P content is 2-12 g / L.

7. SnIn as claimed in claim 1 4 S 8 @FeNi 2 Application of P hollow nanorod composites in photocatalytic hydrogen production.

Citation Information

Patent Citations

  • Multi-metal phosphide nanotube catalyst with evenly distributed catalytic centers and low-temperature preparation method

    CN107252700A

  • Preparation method of CdIn2S4 nano-block / SnIn4S8 sheet-shaped stacking structure bifunctional composite photocatalyst

    CN111203234A

  • FeNiP hollow material and preparation method and application thereof

    CN114855207A

  • Synthetic method of open type hollow FeCoNiP-coated CQDs nanotube structure for electrolyzing seawater

    CN115323428A

  • Bifunctional electrolyzed water catalyst as well as preparation method and application thereof

    CN115928133A

Cited By

  • FeNi2P / PCN-NaCA photocatalyst as well as preparation method and application thereof

    CN121222465A

  • FeNi2p / pcn-na ca photocatalyst, and preparation method and application thereof

    CN121222465B